Stories of China and India - Zheng Ruixiang (You and Us, 2016)
This book tells a lot of stories about friendly exchanges and cooperation between the two peoples to recall this deep friendship. The authors of these stories include diplomats working for a long time in India, and experts, scholars and journalists engaged in research on India and Sino-Indian cultural exchanges as well as Indian friends committed to Sino-Indian friendship and working in China for a long time. It fully reflects the historical origin of Sino-Indian friendship for thousands of years and the promising development prospects. It is advisable for every person engaged in and concerned about Sino-Indian relations to read and treasure this book.